2018
DOI: 10.1002/jsfa.9202
|View full text |Cite
|
Sign up to set email alerts
|

Potential of lactic acid bacteria to modulate coffee volatiles and effect of glucose supplementation: fermentation of green coffee beans and impact of coffee roasting

Abstract: Lactic acid fermentation of green coffee beans is a new strategy for coffee flavor modulation, creating novel aroma characteristics. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The steady increase in lactic acid content is correlated to LAB growth that display fermentative metabolism with usually lactic acid as the main metabolic end product 37 . This is also an important end-metabolite associated with coffee fermentation, which assist in the coffee-pulp acidification process without interfere in the product final quality 32,36,49,50 .…”
Section: Resultsmentioning
confidence: 99%
“…The steady increase in lactic acid content is correlated to LAB growth that display fermentative metabolism with usually lactic acid as the main metabolic end product 37 . This is also an important end-metabolite associated with coffee fermentation, which assist in the coffee-pulp acidification process without interfere in the product final quality 32,36,49,50 .…”
Section: Resultsmentioning
confidence: 99%
“…Yeast exhibit different metabolic processes and secrete different types of extracellular enzymes during fermentation, suggesting that fermentation of green coffee beans with suitable yeast species would modify the flavor precursors and volatile profiles (Lee et al, 2017). This suggestion has not been deeply explored for bacterial starters, because there are a few reports involving bacteria starters and only LAB was used (Wang et al, 2018). The volatiles identified after 0, 24, and 48 h of wet fermentation for every treatment and control are illustrated on Table 2 and their PCA is on Figure 4, 5.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast can also inhibit mycotoxigenic fungal growth, as demonstrated by Souza et al (2017). Few works implementing bacterial starters in coffee have been conducted, most of them use lactic acid bacteria (LAB) such as Wang et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the major volatiles found, pyrazines, furans, ketones, aldehydes, higher alcohols, esters, and sulphur compounds can be highlighted [45][46][47]. Although some of these flavor-active compounds originate from the beans itself, recent studies have revealed that microbial-derived metabolites can also diffuse into the beans [11,14,27,33,[48][49][50]. Upon characterization of the volatile composition of fermented coffee beans, it was observed that inoculation of P. fermentans and P. acidilactici, both in pure and combined treatments, resulted in the modulation of the volatile constitution of coffee beans.…”
Section: Coffee Beans Chemical Compositionmentioning
confidence: 99%
“…The sugars present in the mucilage support microbial, especially yeasts and lactic acid bacteria [10]. Recent studies have been dedicated to the use of yeast and lactic acid bacteria (LAB) as pure starter cultures in post-harvest processing, in order to reduce the time required for fermentation and modulate the chemical and sensory characteristics of coffee beans [11][12][13][14]. Among the selected microorganisms, it is possible to highlight the yeast Pichia fermentans YC5.2 and the lactic acid bacteria Pediococcus acidilactici LPBC161, which are cultures with characteristics of efficient consumption of coffee pulp-sugars and adaptability to the stress factors of coffee processing [15,16].…”
Section: Introductionmentioning
confidence: 99%